Reproductive Characteristics of Chios Ram Lambs During the First Year of Life in Rural Farm Conditions - Funda Erdoğan Ataç; Mustafa Kaymakçı (Journal of Agricultural Sciences, 2021)
This study was conducted to determine some of the reproductive characteristics of young Chios rams. For the purposes of this study, the data was obtained and used from 30 Chios ram lambs born in 2009 between the ages of 90-360 days. The minimum and maximum values of the testicular diameter (cm) and length (cm), scrotal circumference (cm), scrotal length (cm), testicular volume (cm3) of the Chios ram lambs were 1.59-7.30, 3.05-14.23, 12.00-37.50, 7.00-32.00, 17.39-771.44, respectively. Phenotypic correlations between all testis characteristics were found to be statistically significant (P<0.01). The average testosterone hormone in Chios ram lambs was observed to be 7.05 ± 0.31 ng x ml-1. The ejaculate volume, sperm density, progressive motility ratio, immotility ratio, general averages of the ratio of dead spermatozoa and mass movement- consistency of sperm values were examined on sperm of ram lambs at 240, 270, 300 and 330 age of days. Mean values of these traits were obtained as 1.37 mL; 3.95 x 109 mL-1, 82.20 %, 7.07 %, 10.73 % and 4.40-4.09, respectively. Moreover, progressive motility, the effect of live weight and age in other sperm characteristics was found statistically nonsignificant (P>0.05). The testicular diameter and volume, scrotal circumference and scrotal length enlarged related with positively the rate of the sperm motility. As a result, estimating the rate of live spermatozoa of the ram lambs by taking morphological measurements at an early age can be useful. Therefore, this information was vulnerable in indirect selection programs.